Penerapan Model Problem Based Learning dengan Socioscientific Issues untuk Meningkatkan Keterampilan Berpikir Kritis pada Pembelajaran Biologi SMA - Khoirunnisa, Rif'atin; Nugroho, Anwari Adi; Hanik, Nur Rokhimah (Florea : Jurnal Biologi dan Pembelajarannya, 2023)
One of the skills in the 21st century in learning that must be possessed by students is skills in critical thinking, but in reality critical thinking skills at the level of high school education are still relatively low. The purpose of this research is to improve the critical thinking skills of class X high school students by using the Problem Based Learning model accompanied by Socioscientific Issuess. This research is a classroom action research which has 4 stages, including planning, action, observation and also reflection. The subjects of this study were 34 students of class X SMA Negeri in Sukoharjo. Data on critical thinking skills was taken at the end of each cycle. Data collection techniques in this study used observation, tests/assessment techniques, and documentation. The data analysis technique in this study is to use comparative descriptive. The results of the research on students' critical thinking skills scoring showed that in cycle I it was obtained by 41% (14 students), in cycle II it was obtained by 73% (25 students), and in cycle III it was obtained by 91% (31 students). These results indicate an increase in students' critical thinking skills has increased from cycle I to cycle III by 50%. So it can be concluded that the application of the Problem Based Learning model with Socioscientific Issuess can improve students' critical thinking skills.